Extremely obese (BMI > 40 kg/m(2)) and their impact on pregnancy: A 6 months retrospective review in Hospital Ampang, Malaysia - Khalid, S; Masri, MA; Muhammad Shamsir Mohd Aris; Zulkhifli, ND; Narayan, G; Ganesalingam, M (Wiley-Blackwell, 2024)
Indexed by WOS